Comparative evaluation of a website for drug incompatibility: Stabilis, Trissel's Handbook and the currently available tools in Japan. Issue 1 (January 2018) - Suzuki, Shinya; Mochizuki, Nobuo; Iwamoto, Aya Ikeuchi; Yoshida, Mikinori; Murakami, Akio; Ikegawa, Kiwako; Yamaguchi, Masakazu; Vigneron, Jean
Abstract: Background: This study was conducted to evaluate the benefit of Stabilis through a survey of the listings of incompatibility data. Methods: The review was performed in December 2014 to compare the number of incompatible drugs cited by the Stabilis website, "Injectable Drug Audit Manual, 4th edition" (AM) and "Handbook on Injectable Drugs, 17th edition" (ID). We used the data on incompatible drugs to compare each database. We selected 10 frequently used anticancer medicines to compare the drugs cited in Stabilis, AM and ID. In addition, we compared Stabilis and AM in 23 frequently used antibiotics as an additional evaluation. Results: Stabilis had 678 drugs including 456 injectable drugs, AM had 496 injectable drugs and ID had 332 injectable drugs, as of December 2014. Compared with the fact that most references in AM were unofficial data from manufacturers, Stabilis cited 1722 references and ID cited 2830 references. For the 10 selected anticancer drugs, the total number of listed drugs was 118 in Stabilis, compared to 51 in AM and 82 in ID. Overall, mean and median duplication rates were 4.5% and 0% in AM and 60.7% and 59.0% in ID, respectively. For the 23 selected antibiotics, the total number of listed drugs was 463 in Stabilis, compared to 238 in AM. Overall, mean and median duplication rates were 20.1% and 16.0% in Stabilis and 10.3% and 8.0% in AM, respectively. Conclusions: Stabilis offers a beneficial database for checking drug incompatibilities in a manner similar to ID.